Die ideologiese funksie van ruimte in die Markus-vertelling: "n Verkenning - Eck, E. van (Hervormde teologiese studies, 1991)
The ideological function of space in the narrative of Mark: A survey The aim of this article is to investigate the ideological perspective of the narrator on the topographical level in Mark’s narrative. Emphasis is placed on Galilee, Jerusalem, the way, house, town, synagogue and temple, as well as space that is put by the narrator into the mouth of Jesus as focal space in the Gospel. The conclusion is made that the ‘way’ (from Galilee to Jerusalem) must be seen as the most important focal space in the Gospel, which also gives expression to the ideological perspective of the narrator as following Jesus in suffering.